Support and assessment for Fall Emergency Referrals (SAFER 1): cluster randomised trial of computerised clinical decision support for paramedics - Quinn, Terence J.; Snooks, Helen Anne; Carter, Ben; Dale, Jeremy; Foster, Theresa; Humphreys, Ioan; Logan, Phillipa A.; Lyons, Ronan Anthony; Mason, Suzanne Margaret; Phillips, Ceri James; Sanchez, Antonio; Wani, Mushtaq; et al. (Public Library of Science, 2014)
Objective: To evaluate effectiveness, safety and cost-effectiveness of Computerised Clinical Decision Support (CCDS) for paramedics attending older people who fall.